The Poll for an Assistant Minister for the Parish of St. Peter Mancroft, Norwich - Anonymous (Salt Lake City, UT : Project Gutenberg, 2011)
"The Poll for an Assistant Minister for the Parish of St. Peter Mancroft, Norwich" is a historical document published in the mid-19th century, specifically in 1845. This publication is not a novel or a narrative work but rather serves as a record of a polling event that took place to elect an assistant minister for the parish. The focus of the book is on the candidates vying for the position, detailing the number of votes received alongside a comprehensive list of ratepayers who participated in the poll. The book presents the election between two candidates: Rev. Thomas Wilson and Rev. Thomas Clowes, each supported by different factions within the community$1 (BWilson by the Friends of the Established Church and Clowes by the Dissenting Interest. The extensive list that follows outlines numerous voters from various streets in Norwich, indicating the level of community involvement in the electoral process for ecclesiastical leadership. Through this documentation, the book captures a moment of civic engagement and religious governance, reflecting the political and social structure of the time. (This is an automatically generated summary.)s
Release date is 2011-05-09
Transcribed from the 1845 Stevenson and Matchett edition by David Price
Keywords: Church of St. Peter Mancroft (Norwich, England); Clergy -- England -- Norwich